Factors Related to Weight Gain in DMPA (Depo Medroxy Progesterone Acetate) Acceptors - Adisti Rosadi, Della; Dinengsih, Sri; Suciati, Anni (Universitas Islam Lamongan, 2023)
In Indonesia, injectable contraceptives are contraceptives that are in demand, about 34.3% of which are used by women of childbearing age. One of the shortcomings of DMPA hormonal injectable contraceptives is weight gain due to the presence of hormones that facilitate the change of carbohydrates and sugar into fat and stimulate the appetite control center in the hypothalamus which causes acceptors to eat more than usual. This study is to analyze the factors associated with weight gain in DMPA acceptors at TPMB